Assessment of the diagnostic role of annexin A2 (ANXA2) and insulin-like growth factor-1 as serum markers for hepatocellular carcinoma. Issue 1 (January 2016) - Abou-Elela, Dalia H.; Abdel Sameea, Eman; Fakhry, Tamer
Abstract : Background: Hepatocellular carcinoma (HCC) is the fifth most common cancer and the second leading cause of cancer-related deaths worldwide. Objectives: The aim of this study was to assess the diagnostic utility of annexin A2 (ANXA2) and insulin-like growth factor-1(IGF1) in HCC in comparison with α-fetoprotein (AFP). Patients and methods: The study included 90 participants categorized into three groups. Group I (HCC) included 35 patients presenting with HCC. Group II (cirrhosis) included 25 cirrhotic patients without HCC. Group III (controls) included 30 apparently healthy individuals. Levels of AFP, IGF1, and ANXA2 were analyzed in all participants. Results: The median levels of ANXA2 (ng/ml) were significantly higher in the HCC group compared with the cirrhosis and control groups (87, 19.5, and 8.6, respectively, P <0.001). However, median levels of IGF1 (ng/ml) were significantly lower in the HCC group compared with the other two groups (HCC: 95, cirrhosis: 122, and controls: 178.5, P <0.001). ANXA2 had the best area under the curve for the diagnosis of HCC, followed by IGF1 and AFP (0.88, 0.79, and 0.74, respectively). At a cutoff of 65.5 ng/ml for ANXA2 and 114 ng/ml for IGF1, HCC could be diagnosed with a sensitivity of 94.3 versus 80% and specificity of 84 versus 72%, respectively. Adding AFP to IGF1 and ANXA2 increased the sensitivity and decreased the specificity of the former but did not improve the sensitivity of the latter. Conclusion: ANXA2 and IGF1 could be used as serum biomarkers for HCC screening.